Pengaruh Citra Merk, Kualitas Produk, Harga dan Kepuasan Konsumen terhadap Keputusan Pembelian Produk Wet Tisu Passeo - Sitorus, Santa Lusianna; Firmawati, Yeni (JUBISMA, 2023)
The purpose of this study was to determine the effect that brand image, product quality, price and consumer satisfaction on the purchased decision of wet tissue Passeo at Cikupa district Tangerang. The population in this study is buyers or users of wet tissue Passeo at Cikupa district Tangerang. Respondents who were sampled as many as 100 people and conducted with a purposive sampling technique. This study used multiple linear regression analysis. The result showed the brand image, product quality, price and consumer satisfaction have a positive effect on the purchased decision, this means the brand image, product quality, price and consumer satisfaction encourage consumer to make decision of purchased.